Muertes violentas en la capital de la Monarquía. Siglo XVIII - Duñaiturria Laguarda, Alicia (Cuadernos de Historia del Derecho, 2007)
This article analyses the different types of murder (except manslaughter) based on the criminal proceedings examined in the Sala de Alcaldes de Casa y Corte of Madrid. These violent deaths offer a singular insight into Madrid’s society, as well as the mixture of relationships and hates that intertwined in Spain’s capital of the Spanish monarchy during the 18th century.